Preliminary Study of Actinomycetes as Potential Biocatalyst in Biodiesel Production Through Microbial Lipase Activity - Aidha Zulaika; Sari Sekar Ningrum; Dody Guntama (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
Biocatalysts are biological substances that act as an accelerator of chemical reactions without causing influence on the living organism chemically. Biocatalysts based on renewable sources, biodegradable, tolerance to pH and temperature, and high selectivity to stereochemistry substrates and products. The utilization of biocatalyst is environmentally friendly and effective in production costs. This research aimed to determine the potential of actinomycetes as a biocatalyst in biodiesel production. This research method isolation and identification of actinomycetes isolates, conducting lipase activity test to determining lipase enzyme production of actinomycetes isolates. The data analysis in microbial identification was conducted by molecular identification by Gene bank through Basic Local Alignment Search Tool (BLAST). The lipase activity of actinomycetes analyzing by the value of lipase rate of test microbes. Based on chemical analysis of lipase activity, this research results show that actinomycetes T1A has the highest lipase activity by 14.4640 mU/g. Based on molecular identification analysis, actinomycetes T1A was identified as Streptomyces sp., 99% similar to Streptomyces phaeochromogenes.